Pengaruh Sektor Pariwisata dan Human Capital Terhadap Ketimpangan Pendapatan di Kawasan Timur Indonesia - heris kencana; zumaeroh zumaeroh; diah retnowati (FEB UNWIKU PURWOKERTO, 2021)
The purpose of this study was to analyze the relationship between the variables of the tourism sector and human capital on income inequality in Eastern Indonesia. The objects of this research are 12 provinces that are included in the Eastern Indonesia Region (KTI) from 2010-2019. The method used in this study is the panel data regression method. The results of this study indicate that local or domestic tourists and health have no effect on income inequality in Eastern Indonesia from 2010 to 2019. Meanwhile, foreign tourists and education have a negative and significant impact on income inequality in Eastern Indonesia from 2010 to 2019 The implication that can be applied is that the government can develop human resources and create labor-intensive jobs for the lower middle class. Keywords: Income Inequality, Tourism, Human Capital, Eastern Indonesia